MULTIKULTURALISME SEBAGAI MODEL INTEGRASI ETNIS TIONGHOA Dl INDONESIA - Hendro, Eko Putro (Sabda: Jurnal Kajian Kebudayaan, 2013)
The politics of ethnic assimilation and discrimination, especially one which was directed toward Tionghoa ethnic during the Old Order as well as the New Order, has resulted in social conflicts which threatens the process of national integration. Multiculturalism approach is a strategic offer to support the emergence of new social institutions to support the effort of developing civil society in Indonesia. Through the multiculturalism approach, recent stereotypical views, which have triggered conflicts, can be eliminated and the existence of Tionghoa ethnic group, including their presence as citizens, can be appreciated and respected. In that manner, the conflicts can be eliminated and altered into a mutualistic-simbiosist relation,